Syirkah Ainan dalam kerja sama Nelayan Desa Sampulungan - Ardhina Nur Aflaha; Supriadi Muslimin; Ammar Munir; Hasriani Hasriani (Al-Azhar Journal of Islamic Economics, 2021)
The purpose of this study was to determine the shape of the match between the fishermen's cooperation in the village Sampulungan and syirkah ainan. It is a qualitative descriptive study. The research is conducted in the village Sampulungan district northern Galesong district Takalar. The approach used is both the phenomenon approach and the Islamic economy approach. Data collection methods include interviews, observation and documentation. The data gathered is analyzed through several phases of data reduction, the presentation of data and the deduction phase. The population of this study included the businessman, courtier and cabbage from the village Sampulungan subdistrict northern Galesong by the method of a snowball sampling. The results of this study indicate that the role of fishing in the village of Sampulungan was matched by the syirkah ainan.